Kooperatif Tipe Jigsaw: Upaya Meningkatkan Hasil Belajar Bahasa Indonesia Materi Menulis Ringkasan Cerita di Kelas VSDS An-Nuriyah Jakarta Selatan - Okta Rosfiani; Zaqyatul Fitri; Abidzar Algifari; Irma Srirantika (Journal on Education, 2025)
This study aims to explore the effectiveness of the jigsaw-type cooperative learning model in improving student learning outcomes in the Indonesian language subject, particularly in writing story summaries. The issue raised is the low learning outcomes of students caused by the conventional teaching method, which is less interactive. This research uses the Classroom Action Research method. Data collection was conducted through tests and observations to assess interactions during the learning process. The research results show that the implementation of the jigsaw model significantly improves the average learning outcomes of students, as well as enhances their engagement and motivation in the learning process. Thus, the jigsaw model has proven to be an effective alternative for improving the quality of learning in the fifth grade at SD Islam An-Nuriyah, South Jakarta